A layered structure approach to assure urban air mobility safety and efficiency - Gordo, Victor; Becerra, Ines; Fransoy, Alejandro; Ventas, Enrique; Menendez-Ponte, Pablo; Xu, Yan; Tojal, Marta; Perez-Castan, Javier; Pérez Sanz, Luis (MDPI, 2023)
The demand for air mobility services will depend on the safety of these operations but also on the transportation time savings in congested urban areas. An adequate air space structure is therefore essential to achieve both objectives. Corridors, the most extended solution proposed nowadays, can meet the safety requirements necessary for air taxi operations, but they are rigid (point-to-point solutions) and would increase delays. As an alternative, this paper presents the airspace structure proposed in the SESAR AMU-LED Project, based on layers to assure both safety and efficiency of air taxi operations. In this proposal, small UAS will fly in the bottom part, called the Very Low Level, whereas air taxis will fly in the upper part. The paper applies a collision risk model to determine the minimum required safety buffer between both layers to assure the necessary safety levels. The results obtained show that a buffer of 10 m between them would meet the required safety levels for air taxi operations.
Keywords: UAM; eVTOL; U-space; layers; structure; airspace; collision risk; safety buffer